Optimizing Maritime Training Participant Satisfaction: The Mediating Role of Perceived Value and Fees - Muhammad Darwis; Ahmad Yusuf Ismail (CV Edujavare Publishing, 2026)
Competent maritime human resources are crucial for the success of the maritime transportation industry. The Surabaya Maritime Polytechnic faces the challenge of unstable training participant numbers due to intense competition. This study aims to analyze the influence of service quality, infrastructure, and training rates on customer satisfaction, with perceived value as an intervening variable. The research method uses a quantitative explanatory approach through Structural Equation Modeling based on Partial Least Squares with SmartPLS. Data were collected using a questionnaire from one hundred and fifty respondents using a purposive sampling technique. The results analyze the direct and indirect relationships between variables to formulate a service model. In conclusion, strengthening perceived value supported by excellent service quality, adequate facilities, and proportional rates is a key strategy for increasing satisfaction. These results are crucial as managerial recommendations for institutions in making sustainable strategic decisions.